THE POSSIBILITIES OF MODERN ULTRASOUND IN THE DIAGNOSIS OF ECTOPIC PREGNANCY OF VARIOUS LOCALIZATIONS (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2026)
Timely diagnosis of ovarian pregnancy often allows for organ-preserving surgical treatment. In our experience, 4 of 7 cases of ovarian ulcer required only ovarian resection, preserving all reproductive organs. In the remaining 3 cases, adnexectomy was necessary due to significant necrotic changes in the adnexa due to late diagnosis and total hemorrhagic ovarian imbibition.